2021
DOI: 10.3390/risks9020029
|View full text |Cite
|
Sign up to set email alerts
|

What Best Predicts Corporate Bank Loan Defaults? An Analysis of Three Different Variable Domains

Abstract: This paper aims to compare the accuracy of financial ratios, tax arrears and annual report submission delays for the prediction of bank loan defaults. To achieve this, 12 variables from these three domains are used, while the study applies a longitudinal whole-population dataset from an Estonian commercial bank with 12,901 observations of defaulted and non-defaulted firms. The analysis is performed using statistical (logistic regression) and machine learning (neural networks) methods. Out of the three domains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…While SDEFAULT directly reflects the financial difficulties at the moment a firm should finally have submitted the annual report, LDEFAULT provides a longer retrospective view. In Estonia, no all-inclusive information about defaults to the private sector (e.g., banks, suppliers, workers) is available, but as firms having such private defaults usually witness tax arrears [60], the latter normally before the defaults to the private sector, the lack of such information is not an issue.…”
Section: Methodsmentioning
confidence: 99%
“…While SDEFAULT directly reflects the financial difficulties at the moment a firm should finally have submitted the annual report, LDEFAULT provides a longer retrospective view. In Estonia, no all-inclusive information about defaults to the private sector (e.g., banks, suppliers, workers) is available, but as firms having such private defaults usually witness tax arrears [60], the latter normally before the defaults to the private sector, the lack of such information is not an issue.…”
Section: Methodsmentioning
confidence: 99%
“…A significant strand of literature has found that intelligent models in credit default prediction models are efficient in predicting corporate defaulting [20,[26][27][28]. Without the strict assumptions of the traditional statistical models (e.g., independence and normality among predictor variables), intelligent techniques can automatically derive knowledge from training data [28][29][30].…”
Section: Credit Default Prediction Modelsmentioning
confidence: 99%
“…In general, relative to statistic models, the corporate default prediction performance of intelligent techniques is better. For instance, Kim et al [20] found that the neural network model outperforms logit regression. Similarly, Lahmiri [31] documented that SVM is significantly more accurate than a linear discriminant analysis classifier.…”
Section: Credit Default Prediction Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current threats and risk management systems are key CSR factors for Stakeholders and the country's economy. Polish and EU economic disruptions may also affect energy company performance; fuels, gas, and mining companies; project subcontractors, and customers e.g., [20][21][22][23]. It is thus important to identify new energy company risks.…”
Section: Introductionmentioning
confidence: 99%